KUALITAS DAN PROFIL MIKROBA DAGING SAPI LOKAL DAN IMPOR DI DILI-TIMOR LESTE - V., OLIVEIRA,; KRISTINA DEWI, G.A.M.; SURIASIH, K. (Majalah Ilmiah Peternakan; Vol 20 No 3 (2017): Vol 20, No 3 (2017), 2017)
ABSTRACT This study aims at determining the beef quality and microbes profile of local and import beef marketed at Timor Leste. It is conducted using a completely randomized design (CRD) with two treatments of local and import beef at nine markets as the location and taken three times in each market. The variables observed were the physical quality of meat (pH, cooking lose of meat, water holding capacity, meat color) and chemical quality i.e. protein level, meat content of water and microbial profile (total of microbe, E.coli and Coliform). The results showed that pH of local beef, cooking shrinkage, water holding capacity, meat protein were 20.37% (P <0.01), 10.11% (P> 0.05), 50.62% ( P <0.01) and 9.08% (P <0.05) were lower than imported beef while the meat color and meat moisture content were higher by 35.14% (P <0.01) and 53% (P> 0.05), respectively. Total microbe of local beef, total E. coli of meat and total of Coliform respectively 45.16% (P <0.05), 79.59% (P <0.05) and 51% (P <0.05) markedly higher than imported beef. It can be concluded that the means showed good quality of physical local and import beef and existed in the normal score, so they can be consumed. However, total microbe of local and import beef, especially E.coli and Coliform were above standard except E.coli on import beef which was still under the standard of SNI.3932:2008.